ZYGON 'S DUAL MISSION. Issue 1 (March 2014) - Barbour, Ian G.
Abstract The first mission of Zygon has been the exploration of the relation between Religion and Science. The second, I suggest, has been consideration of the relation between Ethics and Technology. Some articles have given attention to the relation of Religion to Ethics, or that of Science to Technology. The interaction of Ethics and Science, and that of Religion and Technology, are also significant. I give examples of articles or symposia in each of these categories and close with great hope for Zygon's future.